Differences in family caregiver experiences and expectations of end-of-life heart failure care across providers and settings: a systematic literature review - Alessandro Valleggi; Claudio Passino; Michele Emdin; Anna Maria Murante (BMC, 2023)
Abstract Heart failure impacts patients' quality of life and life expectancy and significantly affects the daily behaviours and feelings of family caregivers. At the end-of-life, the burden for family caregivers depends on their emotional and sentimental involvement, as well as social costs. Objectives: The aim of this work is to determine whether and how family caregivers' experiences and expectations vary in relation to the places of care and teams involved in heart failure management. Methods: A systematic literature review was conducted, by screening manuscripts dealing with the experience of Family Care Givers' (FCGs) of patients with Advanced Heart failure. Methods and results were reported following the PRISMA rules. Papers were searched through three databases (PubMed, Scopus and Web of Science). Seven topics were used to synthetize results by reporting qualitative information and quantitative evidence about the experience of FCGs in places of care and with care teams. Results: Thirty-one papers, dealing with the experience of 814 FCGs, were selected for this systematic review. Most manuscripts came from the USA (N = 14) and European countries (N = 13) and were based on qualitative methods. The most common care setting and provider profile combination at the end of life was home care (N = 22) and multiprofessional teams (N = 27). Family caregivers experienced "psychological issues" (48.4%), impact of patients' condition on their life (38,7%) and "worries for the future" (22.6%). Usually, when family caregivers were unprepared for the future, the care setting was the home, and there was a lack of palliative physicians on the team. Discussion: At the end-of-life, the major needs of chronic patients and their relatives are not health related. And, as we observed, non-health needs can be satisfied by improving some key components of the care management process that could be related to care team and setting of care. Our findings can support the design of new policies and strategies.